EVALUATION OF REGIONAL GOVERNMENT POLICY ON SPATIAL PLANNING IN THE TUKAD BADUNG RIVER SETBACK AREA, DENPASAR CITY - Tjokorda Gede Dharmawangsa; I Wayan Sudemen; Nyoman Sumawidayani (Jurnal Widya Publika, 2026)
The riparian zone of the Tukad Badung River has experienced significant degradation due to the massive pressures of urbanization in Denpasar City. Approximately 64.8% of the river's total length of 15.39 kilometers has undergone land-use conversion. A total of 419 buildings have been identified within the riverbank area, of which 354 units (84.5%) are considered non-compliant with the regulations governing protected riparian zones. This condition contradicts Denpasar City Regional Regulation Number 8 of 2021 concerning the Regional Spatial Plan (RTRW) 2021–2041, which designates riverbanks as protected areas. This study aims to evaluate the implementation of local government policies regarding spatial planning management in the Tukad Badung River riparian zone. The research employed a descriptive qualitative approach, with data collected through field observations, in-depth interviews with six key informants, and document analysis. Data were analyzed using William N. Dunn’s (2003) public policy evaluation model, which encompasses six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings reveal that policy implementation has not yet been optimal. Only 16 buildings (3.3%) fully comply with the established regulations; inter-agency coordination remains weak; only 14 officers are responsible for monitoring the 15.39-kilometer river corridor; regulatory enforcement is inconsistent; and community participation remains limited. The study recommends strengthening cross-sector coordination, intensifying public awareness and socialization programs, empowering riverbank communities, developing equitable relocation programs, and enforcing regulations in a firmer and more consistent manner. Keywords: : Policy Evaluation, Spatial Planning, River Buffer Zone